Sacral neuromodulation of nociceptive bladder overactivity in cats. Issue 5 (29th August 2016) - Zhang, Zhaocun; Bandari, Jathin; Bansal, Utsav; Shen, Bing; Wang, Jicheng; Lamm, Vladimir; Roppolo, James R.; de Groat, William C.; Tai, Changfeng
Abstract : Aims: To investigate the effects of electrical stimulation of sacral dorsal/ventral roots on irritation‐induced bladder overactivity, reveal possible different mechanisms under nociceptive bladder conditions, and establish a large animal model of sacral neuromodulation. Methods: Intravesical infusion of 0.5% acetic acid (AA) was used to irritate the bladder and induce bladder overactivity in cats under α ‐chloralose anesthesia. Electrical stimulation (5, 15, or 30 Hz) was applied to individual S1–S3 dorsal or ventral roots at or below motor threshold intensity. Repeated cystometrograms (CMGs) were performed with/without the stimulation to determine the inhibition of bladder overactivity. Results: AA irritation induced bladder overactivity and significantly ( P  < 0.05) reduced the bladder capacity to 62.6 ± 11.7% of control capacity measured during saline CMGs. At threshold intensity for inducing reflex twitching of the anal sphincter or toe, S1/S2 dorsal root stimulation at 5 Hz but not at 15 or 30 Hz inhibited bladder overactivity and significantly ( P  < 0.05) increased bladder capacity to 187.3 ± 41.6% and 155.5 ± 9.7% respectively, of AA control capacity. Stimulation of S3 dorsal root or S1–S3 ventral roots was not effective. Repeated stimulation of S1–S3 dorsal root did not induced a post‐stimulation inhibition. Conclusions: This study established a cat model of sacral neuromodualation of nociceptive bladder overactivity. The results revealed that the mechanisms underlying sacral neuromodulation are different for nociceptive and non‐nociceptive bladder activity.